TATA KELOLA PERUSAHAAN YANG BAIK DAN KINERJA KEUANGAN : BUKTI EMPIRIS DARI BANK SYARIAH INDONESIA (BSI) PASCA MERGER - Kuni Naila'L Muna; Ratri Paramitalaksmi (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the differences in Good Corporate Governance (GCG) implementation and financial performance at Bank Syariah Indonesia (BSI) before and after the 2021 merger of Mandiri Syariah, BNI Syariah, and BRI Syariah. Employing a comparative and causal-associative quantitative approach, the study analyzes quarterly financial statements and GCG reports from 2019 to 2024, sourced from OJK and IDX publications. Data analysis utilized descriptive statistics, paired-sample t-tests, and multiple linear regression. GCG variables included the Board of Directors, Board of Commissioners, Sharia Supervisory Board, and Audit Committee, while financial performance was measured by Return on Assets (ROA) and Return on Equity (ROE). The findings reveal significant differences across all GCG components and financial performance indicators pre- and post-merger. Average ROA increased from 1.05% to 1.78%, while average ROE rose from 8.62% to 15.35%. Regression results indicate that the Board of Directors, Board of Commissioners, Audit Committee, and the merger variable had a positive and significant impact on ROA and ROE, whereas the Sharia Supervisory Board had a limited impact. Overall, the merger—supported by stronger corporate governance practices—has enhanced supervisory effectiveness, asset management efficiency, and profitability at BSI. These results demonstrate that the implementation of integrated GCG following the merger has positively contributed to the bank's financial performance.